Peran Bawaslu Dalam Netralitas Aparatur Sipil Negara Pada Pilkada Di Kabupaten Bone (Analisis Siyasah Syar’iyyah) - Ilhamzyah Sandrang; Usman Jafar; Zulhas’ari Mustafa (Danudirja Setyabudi Nusantara, 2025)
This thesis discusses the role of Bawaslu in maintaining the neutrality of the State Civil Apparatus (ASN) in regional elections in Bone Regency from the perspective of Siyasah Syar'iyyah. This study focuses on three main issues, namely: (1) The strategies implemented by Bawaslu in maintaining the neutrality of ASN. (2) The view of Siyasah Syar'iyyah on the neutrality of ASN in the context of supervision carried out by Bawaslu Bone Regency. This study uses a qualitative approach with descriptive analysis methods. The approaches used are theological-normative (sharia) and juridical-sociological. Data were collected from various sources such as Bawaslu Bone Regency, the Subdistrict Supervisory Committee (Panwascam), election observers, political parties, and community leaders. Data collection techniques included observation, interviews, and documentation, which were analyzed through the stages of data reduction, data presentation, and conclusion drawing. The results of the study show that: (1) Bawaslu's strategy in maintaining the neutrality of ASN is carried out through two main approaches, namely prevention and supervision. Prevention is carried out through socialization, distribution of appeal letters, and the use of social media, while supervision is carried out directly in the field and on the use of state or village facilities. (2) From the perspective of Siyasah Syar'iyyah, violations of neutrality by ASN are contrary to the principle of justice, which is one of the main pillars of Islamic government. Such violations not only cause harm to society but also violate the oath of office, which, according to Islamic law, must be obeyed. The implications of this study emphasize the importance of applying political ethics within the framework of Siyasah Syar'iyyah as a normative basis for maintaining the neutrality of civil servants. The government and Bawaslu are expected to increase transparency and accountability in the process of supervision and law enforcement by providing clear and detailed reports on each violation and its follow-up. This is important to strengthen public trust in the democratic process and the integrity of elections.